Dye degradation study of Malachite green and Congo red by using ZnIn2S4. Issue 1 (1st March 2022) - Chand, Mool; Rawat, A.S.; Khanuja, Manika; Rawat, Seema; Ranwa, Mitesh
Abstract: In this manuscript, we demonstrate photocatalytic study of ZnIn2 S4 powder sample under visible light irradiation on Malachite green and Congo red dye. The powder sample was synthesized usingIndium (III) sulphate, thioacetamide andZinc sulphate in aqueous solution. X-ray diffraction and FESEM were used to identify the hexagonal crystal structure and microspheres shape, while UV-Vis spectroscopy was used to acquire absorption and reflectance spectra under visible-light (λ = 420 nm) irradiation, the effects of process factors such as contact duration and adsorbent dose were studied on Malachite green and Congo red. Degradation efficiency of Malachite green and Congo red are 96.33%, 99.79% respectively.The results revealed that visible light photocatalytic degradation of dyes was highly efficient.